An interoperable web-based platform to support health surveillance against latent tuberculosis infection in health care workers and students: The evolution of CROSSWORD study protocol - Angela Rizzi; Eleonora Nucera; Walter Mazzucco; Pierpaolo Palumbo; Domenico Staiti; Umberto Moscato; Francesco Maria De Simone; Michela Sali; Luca Boldrini; Nikola Dino Capocchiano; Stefano Patarnello; Gabriele Rumi; et al. (PLoS ONE, 2025)
Background Tuberculosis (TB) prevention is a major goal in teaching hospital setting. Because of the possible progression or reactivation of latent disease, the screening of both health-care workers (HCWs) and students is an important issue in the TB control program. Objective to deploy a web-based platform interoperating health surveillance systems from different hospitals to define models based on the highlighted risk factors to predict the occurrence of Latent Tuberculosis Infection (LTBI) and to define prevention strategies and interventions. Methods This is a cross-sectional ambispective observational study without drug and device. The primary endpoint is the prevalence of LTBI. The secondary endpoint is the identification of possible risk factors of LTBI in a large cohort of HCWs and students. Conclusions This study aims to enrich the primary prevention measures against TB, having a high socio-economic-health impact in high-risk populations (HCWs and students) through an interoperable digital approach based on data obtained in three large Italian teaching hospitals. ClinicalTrials.gov: NCT05756582